Neurocognitive Impairment in Patients Treated with Protease Inhibitor Monotherapy or Triple Drug Antiretroviral Therapy - Pérez-Valero, Ignacio (Public Library of Science, 2013)
BACKGROUND: In patients who remain virologically suppressed in plasma with triple-drug ART a switch to protease inhibitor monotherapy maintains high rates of suppression; however it is unknown if protease inhibitor monotherapy is associated to a higher rate of neurocognitive impairment. METHODS: In this observational, cross-sectional study we included patients with plasma virological suppression (≥1 year) without concomitant major neurocognitive confounders, currently receiving for ≥1 year boosted lopinavir or darunavir as monotherapy or as triple ART. Neurocognitive impairment was defined as per the 2007 consensus of the American Association of Neurology. The association between neurocognitive impairment and protease inhibitor monotherapy, adjusted by significant confounders, was analysed. RESULTS: Of the 191 included patients - triple therapy: 96, 1–2 years of monotherapy: 40 and >2 years of monotherapy: 55 - proportions (95% CI) with neurocognitive impairment were: overall, 27.2% (20.9–33.6); triple therapy, 31.6% (22.1–41.0); short-term monotherapy, 25.0% (11.3–38.7); long-term monotherapy: 21.4% (10.5–32.3); p = 0.38. In all groups, neurocognitive impairment was mildly symptomatic or asymptomatic by self-report. There were not significant differences in Global Deficit Score by group. In the regression model confounding variables for neurocognitive impairment were years on ART, ethnicity, years of education, transmission category and the HOMA index. Adjusted by these variables the Odds Ratio (95% CI) for neurocognitive impairment of patients receiving short-term monotherapy was 0.85 (0.29–2.50) and for long-term monotherapy 0.40 (0.14–1.15). CONCLUSIONS: Compared to triple drug antiretroviral therapy, monotherapy with lopinavir/ritonavir or darunavir/ritonavir in patients with adequate plasma suppression was not associated with a higher rate of asymptomatic neurocognitive impairment than triple drug ART.